Graham Westbrook Rowley (1912-2003) - MacDonald, J. (ARCTIC, 2004)
Most readers of Arctic will have heard with sadness the news of Graham Rowley's death in Ottawa on December 31, 2003. And many will have read with gratitude the heartfelt tributes his passing occasioned in the press on both sides of the Atlantic, which variously detailed Graham's lifelong, wonderfully eclectic engagement with the Canadian Arctic through exploration, administration, scholarship, and scientific enterprise. Graham's introduction to the Arctic came in 1936. . he seized the chance to join Tom Manning's British Canadian Arctic Expedition (1936-39), which was headed for northern Baffin Island and the largely unexplored east coast of Foxe Basin. . As the expedition's archaeologist, Graham had one main quest, set for him by Diamond Jenness at the National Museum in Ottawa: to unearth conclusive evidence of an ancient Arctic culture quite distinct from the so-called Thule culture described by Danish archaeologist Therkel Mathiassen. . At Avvajja, [near Igloolik Island] he was able to excavate a uniquely "Dorset" site, confirming Jenness's hunch, and establishing the Dorset culture as archaeological fact. He published the results of his archaeological investigations in an article entitled "The Dorset Culture of the Eastern Arctic," which appeared in the American Anthropologist (New Series 42, 1940). . The British Canadian Arctic Expedition left its mark on Igloolik's recorded oral history. Graham and Reynold Bray (who tragically drowned in September 1938) are especially remembered. They both had Inuktitut names, Graham being Makkuktu'naaq ('the little, or likeable, young man'), and Reynold, Umiligaarjuk ('the little bearded one'). A mixture of surprise, amusement, and admiration had greeted their arrival in Igloolik by dog team in February 1937. Here were two young white men, remarkably ill-dressed, lice-infested, walking on the shanks of their skin boots, and almost out of supplies, who had journeyed more or less alone from Repulse Bay, some 200 miles away, in the middle of winter. Even more remarkably, ...